PEMERINTAHAN SULTAN SYARIF HARUN DI KERAJAAN PELALAWAN TAHUN 1940-1945 - Indah, Desi Purnama; ', Isjoni; ', Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Pelalawan kingdom is a kingdom patterned existing Malay coastalarea east coast of Sumatra. Palalawan royal kingdom Pekantua begins with its firstking Maharaja senses and to change its name to the last royal king Pelalawan with thatsultan Syarif harun. Sultan Syarif Harun ruled from 1940-1945. The purpose of thisstudy were (1) to know the history of the Kingdom Palalawan (2) To determine thegeneral picture biography sultan syarif harun in the kingdom Pelalawan (3) Todetermine the appointment of Sultan Syarif Harun became king in the kingdom ofPelalawan (4) To know the reign of Sultan Syarif Harun The Kingdom of Palalawan.This study uses historical method. Results from this study is the reign of Sultan syarifharun lasted for 5 years thereby limiting the sultan to do much against the people andcoupled with the arrival of Japan which further aggravate the situation. Sultan syarifharun open-minded and farsighted forward therefore in the short time that he still hadtime to build a school, a mosque, a sports field and some road in pelalawan. Besides thedifficult conditions under Japanese colony is doing is to do things to protect its peoplefrom the Japanese occupation. Sultan is very loved and respected by his peoplebecause, friendliness, simplicity, humble and generous. Sultan Syarif harun has 3 wivesand of his third child was born the 10 people who live to adulthood.Key word: History, Kingdom.